The role of SOX-2 on the survival of patients with non-small cell lung cancer - Shao, Wenlong; Chen, Hanzhang; He, Jianxing (Journal of Thoracic Disease; Vol 7, No 7 (July 30, 2015): Journal of Thoracic Disease, 2015)
Background: Lung cancer is the most commonly diagnosed cancer as well as the leading cause of cancer death worldwide. Observational studies on the prognostic role of SOX-2 in non-small-cell lung cancer (NSCLC) are controversial. Methods: To clarify the impact of SOX-2 in NSCLC survival, we performed this meta-analysis that included eligible studies. The combined hazard ratios and their corresponding 95% confidence intervals (95% CI) were calculated in terms of overall survival. Results: A total of seven studies with 1,944 patients were evaluable for this meta-analysis. The studies were categorized by histology, disease stage and patient race. Our results suggested that SOX-2 overexpression had a favorable impact on survival of patients with NSCLC, the HR (95% CI) was 0.57 (0.48 to 0.65). However, highly significant heterogeneity was detected among these studies (I2=76.7%, P=0.000). Conclusions: SOX-2 overexpression indicates a favorable prognosis for patients with NSCLC.